Three-dimensional printing: Fine-tuning of the face of pediatric dentistry - Rishi Tyagi; Namita Kalra; Amit Khatri; M Khadeeja Kulood; Neetu Garg (Wolters Kluwer Medknow Publications, 2022)
The incessant exploration of technology in the segment of health care and medicine has paved a way to herald the dawn of three-dimensional (3D) and four-dimensional imaging technologies in dentistry. 3D printing also referred to as solid free-form fabrication is a form of rapid prototyping that utilizes additive manufacturing technology in contrast to the subtractive technique of commonly used imaging technology like CAD/CAM. 3D printing has materialized the fabrication of custom-made products that eliminates the exhaustive artisanal labor techniques with reduced work time. It also escalated the accuracy and precision in the production of intricate human details. The purpose of this review is to procure the data summarizing the applications of novel 3D printing technique in the field of pediatric dentistry harnessing enhancement in technology. Furthermore, it compiles data from various clinical trials providing evidence-based approach for promoting the implementation of the techniques into practice.